Bacteriological Profile and Antibiotic Sensitivity Pattern of Surgical Site Infection Following Gynecologic Oncology Surgery at Hasan Sadikin General Hospital - Mantilidewi, Kemala Isnainiasih; Harsono, Ali Budi; Kireina, Jessica; Pringgowibowo, Jaeni; Al Baihaqi, Windy Natasya (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction: Surgical site infection (SSI) is the most common complication of gynecologic oncology surgeries. Understanding the characteristics, bacteriological profile, and antibiotic sensitivity pattern of SSI patients can help guide patient’s management and reduce morbidity, mortality, and economic burden caused by SSI. The aim of this study is to describe the characteristics, bacteriological profile, and antibiotic sensitivity pattern of SSI patients following gynecologic oncology surgery at Hasan Sadikin General Hospital Bandung in 2021. Methods: This is a descriptive study that analyzed medical records of patients undergoing gynecologic oncology surgery at Hasan Sadikin Hospital Bandung from January to December 2021. Results: Out of 157 gynecologic oncology surgeries in 2021 that met the criteria, there were 11 incidences of SSI (7%). All SSI patients received postoperative antibiotics, with the most common type of antibiotic given being a combination of ceftriaxone and metronidazole. Ten out of the 11 specimens from SSI patients showed bacterial growth and a total of 17 bacterial isolates were found. Most specimens showed polymicrobial infection with the most common isolate being Escherichia coli Extended-Spectrum Beta-Lactamase (ESBL). Gram-positive bacteria in this study were most sensitive to Vancomycin, Tigecycline, and Gentamicin. Meanwhile, gram-negative bacteria were most sensitive to Ertapenem and Meropenem. Conclusion: Incidence of SSI following gynecologic oncology surgery at Hasan Sadikin General Hospital in 2021 is 7%. The most frequently found isolate was Escherichia coli ESBL. Gram-positive bacteria were most sensitive Vancomycin, Tigecycline, and Gentamicin; while gram-negative bacteria were most sensitive to Ertapenem and Meropenem.